HIV related stigma and discrimination among people living with HIV/AIDS in Ernakulam District: A qualitative study - Leyanna Susan George (Wolters Kluwer Medknow Publications, 2019)
Introduction: Human immunodeficiency virus (HIV)-related stigma refers to the negative beliefs, feelings, and attitudes, while discrimination is the unfair and unjust treatment of people living with HIV/acquired immunodeficiency syndrome (PLHA). Their manifestations are context-specific and have varied impacts. Objectives: (1) To determine the different contexts in which PLHA face stigma and discrimination. (2) To study the impact of stigma and discrimination on the health of the PLHA. Methodology: A qualitative study was conducted among PLHA at the office of the network for positives. Fourteen key informant interviews were conducted on PLHA and the peer counselors to determine the contexts in which they faced stigma and discrimination. To understand its impact on health, two Focus Group Discussions were carried out separately for male and female PLHA. The data were collected using a semi-structured interview guide and were audio recorded. They were then transcribed, manually coded, thematically analyzed, and triangulated. Results: The themes that arose showed that stigma and discrimination were context-specific and were experienced in different levels such as an individual, family, community, health-care system, and media. They experienced violence in addition to the loss of shelter and economic support. Stigma and discrimination was found to have a negative impact on the health of the PLHA. It was a major hindrance to health-care utilization resulting in worsening of health conditions and indirectly contributed to the spread of diseases. Conclusion: PLHA experience different forms of stigma and discrimination which have an adverse impact on their health. Behavior change communication initiatives for the community are required.